2004
DOI: 10.1111/j.1471-4159.2004.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2‐like antagonists induce chromatin remodeling in striatal neurons through cyclic AMP‐protein kinase A and NMDA receptor signaling

Abstract: Antipsychotic drugs regulate gene transcription in striatal neurons by blocking dopamine D 2 -like receptors. Little is known about the underlying changes in chromatin structure, including covalent modifications at histone N-terminal tails that are epigenetic regulators of gene expression. We show that treatment with D 2 -like antagonists rapidly induces the phosphorylation of histone H3 at serine 10 and the acetylation of H3-lysine 14 in bulk chromatin from striatum and in nuclei of striatal neurons. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 77 publications
5
95
0
Order By: Relevance
“…Thus, epigenetic marking of the genome can be considered a persistent form of cellular memory by which terminally differentiated cells remember their phenotype. In the past 10 years, different laboratories have reported that histone modifications (acetylation and methylation) and DNA methylation are regulated in adult neurons in association with learning and memory processes (for review, see Roth and Sweatt, 2009;Gupta el al., 2010), as well as in response to seizure (Huang et al, 2002;Tsankova et al, 2004) and psychotropic drugs (Li et al, 2004;Kumar et al, 2005) and in mental disorders (Levenson and Sweatt, 2005). These data suggest that epigenetic regulation also have a critical role in the postmitotic cells function.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, epigenetic marking of the genome can be considered a persistent form of cellular memory by which terminally differentiated cells remember their phenotype. In the past 10 years, different laboratories have reported that histone modifications (acetylation and methylation) and DNA methylation are regulated in adult neurons in association with learning and memory processes (for review, see Roth and Sweatt, 2009;Gupta el al., 2010), as well as in response to seizure (Huang et al, 2002;Tsankova et al, 2004) and psychotropic drugs (Li et al, 2004;Kumar et al, 2005) and in mental disorders (Levenson and Sweatt, 2005). These data suggest that epigenetic regulation also have a critical role in the postmitotic cells function.…”
Section: Discussionmentioning
confidence: 81%
“…More broadly, pharmacoepigenomics, or a drug's direct and indirect effects on chromatin structure and function, may perhaps in the future emerge as an interesting biomarker to predict treatment response, side effects or illuminate novel, hitherto unsuspected mechanisms of drug action. While this prediction is presently highly speculative, it is interesting to note that a wide range of psychoactive drugs, including dopamine receptor agonists (Schroeder et al, 2008), typical and atypical antipsychotics (Huang et al, 2007b;Li et al, 2004), and several mood-stabilizers, including lithium and valproate (Bredy et al, 2007;Dong et al, 2008;Kwon and Houpt, 2010), were shown to affect DNA methylation and/or histone acetylation, phosphorylation, and methylation in selected areas of the forebrain.…”
Section: Psychiatric Epigenetics In the Culture Dish?mentioning
confidence: 99%
“…Given the above, one cannot exclude that at least some of the epigenetic alterations reported in diseased postmortem brain are not necessarily stable imprints that exist for very long periods of time, and instead, could potentially reflect a mechanism that operated on a much shorter time scale before death, perhaps lasting only a few days or even less. The rapidly growling list of conditions acutely affecting the regulation of chromatin structure and function in brain includes ischemia (Endres et al, 2000), and exposure to environmental toxins (Bollati et al, 2007;Desaulniers et al, 2005;Salnikow and Zhitkovich, 2008), nicotine (Satta et al, 2008), alcohol (Marutha Ravindran and Ticku, 2004), psychostimulants (LaPlant et al, 2010;Numachi et al, 2007;Numachi et al, 2004), antipsychotic drugs (Cheng et al, 2008;Dong et al, 2008;Li et al, 2004;Mill et al, 2008;Shimabukuro et al, 2006) and mood stabilizers such as lithium (Kwon and Houpt, 2010) and valproate (Bredy et al, 2007;Dong et al, 2008).…”
Section: Epigenetic Markings In Brainfstate or Trait?mentioning
confidence: 99%
“…In striatopallidal MSNs, haloperidolinduced activation of cAMP-dependent protein kinase A (PKA) and of the protein phosphatase-1 (PP-1) inhibitor, dopamine-and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32), has been proposed to affect gene transcription by acting on nuclear targets, including the cAMP response element-binding protein and histone H3 Konradi and Heckers, 1995;Li et al, 2004;Pozzi et al, 2003). Much less is known about the ability of antipsychotic drugs and of the PKA/DARPP-32 cascade to affect signaling cascades involved in translational control.…”
Section: Introductionmentioning
confidence: 99%